SARS-CoV-2 and the Missing Link of Intermediate Hosts in Viral Emergence - What We Can Learn From Other Betacoronaviruses - Schindell, Brayden G.; Allardice, Meagan; McBride, Jessica A.M.; Dennehy, Brendan; Kindrachuk, Jason (Frontiers in Virology, 2022)
The emergence of SARS-CoV-2 in 2019 has resulted in a global pandemic that has had devastating human health and economic consequences. While the development of multiple vaccines, antivirals and supportive care measures have aided in our efforts to gain control of the pandemic, the emergence of multiple variants of concern and spillover into numerous nonhuman animal species could protract the pandemic and increase the difficulty in predicting future spillback events into the human population as well as the impact of virus evolution as a result of zoonoses. Here, we provide historic context regarding the roles of reservoir and intermediate hosts in coronavirus circulation and discuss current knowledge of these for SARS-CoV-2. Increased understanding of SARS-CoV-2 zoonoses are fundamental for efforts to control the public health impact of COVID-19.